1991
DOI: 10.1111/j.1151-2916.1991.tb06808.x
|View full text |Cite
|
Sign up to set email alerts
|

Cation Interdiffusion and Phase Stability in Polycrystalline Tetragonal Ceria–Zirconia–Hafnia Solid Solution

Abstract: H a k o z a k i , Fukuoka 81 2, Japan Zr-Hf interdiffusions were carried out at 1350" to 1520°C for p o l y c r y s t a l l i n e t e t r a g o n a l s o l i d s o l u t i o n s of l4CeO2.86(Zrl-,Hf,)O2 with X = 0.02 and 0.10. Lattice and grain-boundary interdiffusion parameters were calculated from the concentration distributions by using Oishi and Ichimura's equation. Lattice interdiffusion coefficients were described by D = 3.0 X 1w exp[-623 (kJ/mol)/RT] cmz/s and grain-boundary interdiffusion parameters by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 24 publications
6
36
0
Order By: Relevance
“…The parameters describing the geometry have been obtained experimentally, using mercury intrusion porosimetry and measurements on scanning electron microscope (SEM) micrographs. The surface diffusivity and activation energy are those reported for tetragonal ZrO 2 -3mol%Y 2 O 3 [11], while grain boundary diffusivities are for tetragonal 14CeO 2 -86(Zr 1-x Hf x )O 2 , with x=0.02 and 0.10 [12]. Ω is the volume of the unit cell, calculated from lattice parameters obtained by X-ray diffraction (XRD).…”
Section: S Ss Ss H Y R G H Y R H Y Rmentioning
confidence: 99%
“…The parameters describing the geometry have been obtained experimentally, using mercury intrusion porosimetry and measurements on scanning electron microscope (SEM) micrographs. The surface diffusivity and activation energy are those reported for tetragonal ZrO 2 -3mol%Y 2 O 3 [11], while grain boundary diffusivities are for tetragonal 14CeO 2 -86(Zr 1-x Hf x )O 2 , with x=0.02 and 0.10 [12]. Ω is the volume of the unit cell, calculated from lattice parameters obtained by X-ray diffraction (XRD).…”
Section: S Ss Ss H Y R G H Y R H Y Rmentioning
confidence: 99%
“…In the bicomponent sample, the tetragonal solid solution is formed at a higher temperature. Burger et al [30] demonstrated that this transformation occurs very slowly, because it depends on the diffusion rate of yttria, and the cation diffusion rate in yttria and zirconia is very low [41,42]. The experimental results presented by Burger et al showed that the diffusion-controlled phase transformation plays an important role in the densification behavior and in the inhibition of grain growth.…”
Section: Effect Of Starting Powdersmentioning
confidence: 86%
“…In an extreme case of L5e, instantaneous de-bonding may occur along grain boundaries or interfaces. Using the diffusion data for Ce-doped tetragonal ZrO 2 [31] and an average dihedral angle of 1201, for which s is 0.45, and assuming that n ¼ 3 and s ¼ 30 MPa, we can calculate the critical case (b), for which d c ¼ 3e ¼ 3L. The results of this calculation are shown in Fig.…”
Section: Cavity Nucleationmentioning
confidence: 99%